Making Substantial Connections: A Critical Appreciation of Sheila Delany - Akbari, Suzanne Conklin (Florilegium, 2006)
Centring on three of Delany’s most influential publications, this article provides an overview of the way her work has both engendered debate and stimulated new research directions. "Undoing Substantial Connection" (1972) argues that the late Middle Ages witnessed the decline of "analogical thought" in literature, science, politics, and philosophy; "Mothers to Think Back Through" (1987) engages the life and work of Christine de Pizan, challenging the prevalent celebratory readings of this late medieval writer in order to pose tough questions regarding the role of the author in society; and "Geographies of Desire" (1992) explores the interrelation of gender and Orientalism in the poetry of Chaucer.